2012
DOI: 10.1016/j.arthro.2011.08.305
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of Anatomic Double-Bundle Anterior Cruciate Ligament Reconstruction With Ligament Remnant Tissue Preservation

Abstract: Purpose: The purpose of this pilot study is to clarify the preliminary results of an anatomic double-bundle ACL reconstruction procedure with ligament remnant tissues. Methods:Using the trans-tibial technique, 2 doubled semitendinosus tendons were grafted into 4 tunnels created at the center of each bundle attachment, penetrating the ACL remnant tissue. Forty-four patients (27 men and 17 women) with an isolated ACL injury underwent ACL reconstruction using this procedure. The mean age of subjects was 29 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 39 publications
2
65
0
Order By: Relevance
“…Currently, OI and TP techniques are popular techniques for drilling femoral tunnels in anatomic ACL reconstruction [8,9,12,20,25,29,30,32,34,51,54,56], and modified TT technique has been also reported to achieve anatomic placement of the grafts within ACL footprint [14,58,59]. Recent studies on GBA evaluated by postoperative CT have reported that OI technique resulted in more steep GBA than in TP technique, with about 80° GBA by OI technique [23,40,50], and these results were similar to our findings at full extension.…”
Section: Discussionsupporting
confidence: 58%
“…Currently, OI and TP techniques are popular techniques for drilling femoral tunnels in anatomic ACL reconstruction [8,9,12,20,25,29,30,32,34,51,54,56], and modified TT technique has been also reported to achieve anatomic placement of the grafts within ACL footprint [14,58,59]. Recent studies on GBA evaluated by postoperative CT have reported that OI technique resulted in more steep GBA than in TP technique, with about 80° GBA by OI technique [23,40,50], and these results were similar to our findings at full extension.…”
Section: Discussionsupporting
confidence: 58%
“…If the remnant preserving technique is performed without any removal of the remnant tissue at the femoral side, it is very difficult to locate the appropriate tunnel position with arthroscopic observation of the frontside of the remnant tissue, since the intercondylar ridge is hard to detect. Therefore, it is often necessary to confirm the tunnel position by X-ray [26]. We performed the standard approach by only residual tissue of the normal femoral attachment area being peeled off as little as possible but enough to detect the intercondylar ridge; however, some extent of the remnant at the femoral side had to be removed.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the remnant preserving technique has been recommended based on the theoretical advantages such as proprioceptive function preservation [20][21][22][23], stability preservation [24,25], and graft healing [26][27][28][29]. A recent study also showed that the remnant tissue can be used for a landmark of anatomic positioning of the tunnels, not only for the tibial side but also for the femoral side [30].…”
Section: Introductionmentioning
confidence: 99%
“…2e5,8,12,17e21 ACL remnants make a biomechanical contribution to AP and rotational knee stability in patients with a complete ACL injury. 6 ACL remnants contributed to AP knee stability evaluated at 30 of knee flexion for up to one year after injury. 22 Adachi et al reported that significantly better results of position sense and joint stability were obtained from ACL augmentation (with remnant preservation) than from conventional ACL reconstruction (without remnant preservation).…”
Section: S76mentioning
confidence: 99%